Experimental Evaluation of Sandy Soil Reinforced with Synthetic Fiber for Bearing Capacity - Fathia Alnaas; Enas B. Altalhe; Samiha Abdelrahman; Manara Al-Naji Abdul Rahim; Wedad Mukhtar Bakir (African Journal of Advanced Pure and Applied Sciences, 2025)
Many sites need to improve the soil before implementing the projects. There are many methods to improve the soil, but some methods have a negative impact on the environment, such as chemical improvement. At the same time, another one is as expensive as replacement soil. Therefore, it was searched for economical ways that are less harmful to the environment. One of the most effective and reasonably priced ways to enhance the characteristics of sandy soil, according to earlier research, is synthetic fiber. This paper’s findings describe the usage of locally sandy soil to increase the stability and bearing capacity of woven jute cloth. The study is to promote the use of geotextile, which has emerged as a significant technique for improving soil in recent years. The investigation shows that bearing capacity factors have significantly improved. This study examines the impact of the layer depth of woven jute geotextile on bearing capacity factors and stability using poorly graded sandy soil SP as defined by ASTM-USCS. Results showed a significant improvement when the jute textile layer is closer to the surface than the penetrating depths, indicating the possibility of obtaining good stability and high resistance. Also, a small distance between the two layers yielded better results than using a large distance.